Fragen zur Genese der naturräumlichen Großeinheiten des Ostseeraumes - Hurtig, Theodor (ERDKUNDE, 1966)
As an introduction, a short classification of the 4 major natural units of the Baltic Sea area is given, worked out by the author purely on the basis of geomorphologie data. A second section deals with several problems in the origin of these major units: the controversial ice isostasy; the importance of orogenic and epeirogenic phases of development of the old Fenno-Scandian Shield for the outflow of material in its peripheral areas; the Pleistocene in the peri-Baltic and the influence of a prequaternary relief upon its contemporary surface picture; the various late and post-glacial stages in the evolution of the Baltic with especial regard to the riddle of the Ancylus Sea; and the testimony of post-diluvial transgression phenomena in different sectors of the Baltic Sea. A detailed list of references can be found at the end of the article.